Coaching Digital Marketing Kepada Redseller Baru: Pendampingan Pemanfaatan Marketplace Facebook dan Tiktok Sebagai Media Promosi Akomodasi Reddoorz: Pengabdian - Sri Surya Tri Mustika; Bowo Santoso (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity takes the form of individual coaching and digital marketing mentoring for a new RedDoorz RedSeller, conducted online through Google Meet in a 1-on-1 coaching format. The facilitator provided structured and interactive personal mentoring throughout the session. The coaching began with an introduction to and step-by-step demonstration of the RedSeller application via screen sharing, covering: the home and dashboard display, promo code creation, hotel search and property detail verification, room stock and type checking, the booking process, payment methods, and customer check-in time selection. Mastery of the RedSeller application served as a critical foundation before the participant progressed to digital promotion strategies, as understanding the booking flow, promo codes, and application system is a prerequisite for conducting effective promotions. Following the application training, coaching continued with digital promotion strategies using Marketplace Facebook and TikTok, encompassing listing creation, title and price determination, description writing, Facebook group utilization, defining TikTok promotion objectives, trend and hashtag research, crafting compelling 3-second hooks, concise captions with calls to action, upload consistency, and optimal upload timing. This activity aims to enhance the digital marketing capabilities of new RedSellers so they can effectively promote RedDoorz accommodations, expand market reach, and improve sales performance and commission earnings. Results indicate increased participant comprehension of both application usage and digital promotion strategies, high enthusiasm and active participation throughout the session, and the effectiveness of the 1-on-1 coaching format in creating a more focused and personalized mentoring experience.